A combined analysis of morphological traits, chloroplast and nuclear DNA sequences within Santiria trimera (Burseraceae) suggests several species following the Biological Species Concept - (:unkn) unknown (My University, 2010)
Background and aims Species delimitation remains a difficult task in many groups of organisms. Even widespread and conspicuous tropical trees make no exception. Santiria trimera, an African rainforest tree, displays substantial morphological variability. While classical analysis of historical herbarium samples lead to the recognition of a single species, two morphotypes of S. trimera are regularly collected in Gabon and Equatorial Guinea, sometimes in sympatry: one form with stilt roots (SR) and another form without stilt roots (NSR). Methods To assess whether these forms constitute distinct taxa and to understand evolutionary processes within African Santiria, we combined a morphological and a spatial analysis of both sympatric morphotypes in northern Gabon with a phylogenetic analysis of samples from West and Central Africa, including the island of Sao Tome. Key results In Gabon, morphological traits, chloroplast DNA (cpDNA) and nuclear DNA (nuDNA) sequences congruently lead to the recognition of two well differentiated and reproductively isolated taxa corresponding to SR and NSR morphotypes. However, rare cases of the SR morphotype bearing DNA sequences typical of NSR individuals suggest that hybridization might sometimes occur. No evidence for habitat specialization of the two taxa was found. DNA sequences from Sao Tome formed monophyletic clades at both marker types and the nuDNA gene tree suggests that the Sao Tome population probably originated from Central Africa and subsequently underwent allopatric differentiation from continental populations. Conclusion In Central Africa, S. trimera is composed of at least two distinct sympatric species following the Biological Species Concept and calls for further morphological and phenological studies and experimental crosses bet
Keywords: African Research